Knowledge Management Enabler (KME) to Promote Innovation Capabilities in Public R&D Centers in Indonesia - Helmi, Rahmi Lestari (The Asian Journal of Technology Management (AJTM), 2020)
Abstract. In the organizational context, innovation capabilities is influenced by knowledge management process. To improve the performance of innovation capabilities, further identification on most influential factors in implementing knowledge management is needed, referred to knowledge management enablers (KME). This study aims to determine the specific factors of KME dimensions affecting innovation capabilities in R&D organization. Furthermore, this study also focuses on the strength and direction of the correlation between KME dimensions of personal, organizational, and technology to innovation capability. Quantitative research approach was conducted and data were taken from 134 respondents of employees/researchers at research centers/units in a public R&D organization. The results show that personal dimension (interpersonal trust and learning motivation) becomes the most significant factor affecting innovation capability in the R&D organization, followed by technological dimension (ICT use,) with a correlation value of 0.44 (? <0.05) and 0.36 (? <0.05) respectively. The results of this study recommend that the governance of knowledge management process in R&D organization should be put mainly on personal dimension as a major driver of innovation.Keywords: Innovation capability, knowledge management enabler (KME), R&D organization